PENGEMBANGAN PERANGKAT PEMBELAJARAN KONSEP BAKTERI DENGAN MODEL INKUIRI PADA SISWA SMA - Nahdhiah Islamiyah (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2019)
Biology learning process that occurs in SMAN 2 Muara Teweh still using devices based learning and student handbooks with the curriculum SBC devices are arranged in the Subject Teachers Council (MGMP). Student handbook based curriculum SBC used as basis for the preparation of such devices in general. Learning with the inquiry model of bacterial material has never been used by teachers in order to improve the learning spirit of students to learn. The material of bacteria is one of the materials related to the scientific attitude. The aim of this study is to produce a software development learning inquiry model with the concept of high school students of class X bacteria valid and practical and can study the implementation of the concept of bacteria using a model of an effective inquiry. Samples were individual trials that test 3 and test experts legibility on 6 students, small groups of test class numbered 19 students and class field tests totaling 24 students. The instrument of this research is the syllabus, lesson plans, worksheets, assessment sheets, key pieces of assessment, teaching materials, process observation sheet, psychomotor skills, critical thinking, character, social behavior and the activities of teachers and students. Data retrieved student learning outcomes through pretest and posttest in learning the concept of bacteria using inquiry model. Activity observation sheet obtained under observation while the activities of the skills assessed by sheets of skills. It can be concluded that Practicality learning device has been reached. the enforceability of RPP and either categorized student activity, student responses almost all the students are very happy. The effectiveness of the learning device has also been met, it is based on the cognitive learning products and cognitive processes has reached mastery that students get the value of N-gain with high category, the assessment results psychomotor skills, assessment of social attitudes and attitude of the character, as well as critical thinking has been included in both categories, research can produce development tools through inquiry model valid, practical and effective.